Plasma concentrations of per- and polyfluoroalkyl substances are associated with perturbations in lipid and amino acid metabolism. (May 2023) - Prince, Nicole; Begum, Sofina; Mínguez-Alarcón, Lidia; Génard-Walton, Maximilien; Huang, Mengna; Soeteman, Djøra I.; Wheelock, Craig; Litonjua, Augusto A.; Weiss, Scott T.; Kelly, Rachel S.; Lasky-Su, Jessica
Abstract: Exposure to per- and polyfluoroalkyl substances (PFAS) through the environment can lead to harmful health outcomes and the development of disease. However, little is known about how PFAS impact underlying biology that contributes to these adverse health effects. The metabolome represents the end product of cellular processes and has been used previously to understand physiological changes that lead to disease. In this study, we investigated whether exposure to PFAS was associated with the global, untargeted metabolome. In a cohort of 459 pregnant mothers and 401 children, we quantified plasma concentrations of six individual PFAS- PFOA, PFOS, PFHXS, PFDEA, and PFNA- and performed plasma metabolomic profiling by UPLC-MS. In adjusted linear regression analysis, we found associations between plasma PFAS and perturbations in lipid and amino acid metabolites in both mothers and children. In mothers, metabolites of 19 lipid pathways and 8 amino acid pathways were significantly associated with PFAS exposure at an FDR<0.05 threshold; in children, metabolites of 28 lipid pathways and 10 amino acid pathways exhibited significant associations at FDR<0.05 with PFAS exposure. Our investigation found that metabolites of the Sphingomyelin, Lysophospholipid, Long Chain Polyunsaturated Fatty Acid (n3 and n6), Fatty Acid- Dicarboxylate, and Urea Cycle showed the most significant associations with PFAS, suggesting these may be particular pathways of interest in the physiological response to PFAS. To our knowledge, this is the first study to characterize associations between the global metabolome and PFAS across multiple periods in the life course to understand impacts on underlying biology, and the findings presented here are relevant in understanding how PFAS disrupt normal biological function and may ultimately give rise to harmful health effects. Graphical abstract: Image 1 Highlights: Age- and exposure-dependent trends were observed in metabolic perturbations to PFAS. Five lipid pathways were consistently altered across mothers and offspring. Seven lipid pathways differed in direction of effect between mothers and offspring. Amino acid metabolism pathways were consistently increased in mothers and children.